2021
DOI: 10.1371/journal.pone.0255073
|View full text |Cite
|
Sign up to set email alerts
|

Modelling chronic malnutrition in Zambia: A Bayesian distributional regression approach

Abstract: Background The burden of child under-nutrition still remains a global challenge, with greater severity being faced by low- and middle-income countries, despite the strategies in the Sustainable Development Goals (SDGs). Globally, malnutrition is the one of the most important risk factors associated with illness and death, affecting hundreds of millions of pregnant women and young children. Sub-Saharan Africa is one of the regions in the world struggling with the burden of chronic malnutrition. The 2018 Zambia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Findings indicated poor household sanitation and poor household wealth index exhibited a predominantly positive influence on under-five children to be stunted. This is also evidenced in some literature [ 19 , 22 , 44 ]. Similarly, when analyzing potential factors that may affect the clustering of under-five stunting, stunting among children in Ethiopia was positively associated with children who had uneducated mothers.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Findings indicated poor household sanitation and poor household wealth index exhibited a predominantly positive influence on under-five children to be stunted. This is also evidenced in some literature [ 19 , 22 , 44 ]. Similarly, when analyzing potential factors that may affect the clustering of under-five stunting, stunting among children in Ethiopia was positively associated with children who had uneducated mothers.…”
Section: Discussionsupporting
confidence: 77%
“…This is supported by previous spatial analysis of under-five stunting conducted previously in Ethiopia [ 24 , 25 , 27 – 30 ]. Furthermore, in the other settings, various pieces of evidence revealed the presence of geographical variation of under-five stunting such as studies conducted in Rwanda [ 44 ], Ghana [ 18 ], Zambia [ 19 ], Nigeria [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has been echoed by Johri et al 2019 who also called into question the relationship between improved water sources and wasting and stunting [36]. Furthermore, the influence of maternal education on children's nutrition appears to hinge on reaching a certain level of educational attainment [37][38][39]. Investigators in a case-control study have also found that maternal employment does not affect a child's nutritional status [40].…”
Section: Discussionmentioning
confidence: 99%